Balancing Global Agricultural Water Supply and Demand - Fraiture, Charlotte de (2011)
The recently completed Comprehensive Assessment of Water Management in Agriculture concluded that globally there are sufficient land and water resources to produce food for a growing population over the next 50 years. But it is probable that today's trends, if continued, will lead to water crises in many parts of the world. Yearly some 7 100 billion cubic meters (m3) of water are evaporated by crops to meet global food demand, equivalent to more than 3 000 litres per person per day. With a growing population, rising incomes and changes in diets, food demand will increase rapidly. Demand for biomass for biofuels will further drive the demand for agricultural products and hence agricultural water. Some forecasts foresee a doubling of agricultural water demand in the coming 50 years. This is reason for concern as already 1.2 billion people live in areas where water is insufficient to meet all demands. Fortunately, there seems much scope to improve productive use of water and get more out of a unit of water. This paper explores forecasts of global agricultural water demand and scenarios to meet this. It concludes with challenges in future water supply.